2019
DOI: 10.1101/735696
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling the impact of environmental and phylogenetic constraints on prokaryotic strain diversity

Abstract: Microbial organisms inhabit virtually all environments and encompass a vast biological diversity. The pan-genome concept aims to facilitate an understanding of diversity within defined phylogenetic groups. Hence, pan-genomes are increasingly used to characterize the strain diversity of prokaryotic species. To understand the interdependency of pan-genome features (such as numbers of core and accessory genes) and to study the impact of environmental and phylogenetic constraints on the evolution of conspecific st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Such transfers are thought to facilitate adaptation to the environment. Consistent with this hypothesis, environment and lifestyle are found to correlate with intra-species genomic variation in prokaryotes 43 . Interestingly, several studies have found that some ribosomal proteins are often transferred 23,33 , which runs against received wisdom and the complexity hypothesis, but is consistent with prior research suggesting that informational genes can in fact undergo lateral gene transfer 44 and appears to confi rm the suspicions of tree of life critics 4 .…”
Section: Lateral Gene Transfer Is Endemic Across the Tree Of Lifesupporting
confidence: 56%
“…Such transfers are thought to facilitate adaptation to the environment. Consistent with this hypothesis, environment and lifestyle are found to correlate with intra-species genomic variation in prokaryotes 43 . Interestingly, several studies have found that some ribosomal proteins are often transferred 23,33 , which runs against received wisdom and the complexity hypothesis, but is consistent with prior research suggesting that informational genes can in fact undergo lateral gene transfer 44 and appears to confi rm the suspicions of tree of life critics 4 .…”
Section: Lateral Gene Transfer Is Endemic Across the Tree Of Lifesupporting
confidence: 56%
“…Recently, prokaryotic pan-genomes have crossed species and even phyla boundaries, including one study using 7,104 genomes from ten prokaryotic phyla 79 . Due to the small size of haploid prokaryotic genomes such studies are computationally feasible.…”
Section: Prospects and Future Directionsmentioning
confidence: 99%
“…S7B). While pangenome sizes are known to vary between species (15,17,34), it is intriguing to find such extensive gene content variation within a single population and local source. These results also corroborate observations from a previous study of another large Sal.…”
Section: Discussionmentioning
confidence: 99%